Polymer Capsules: Versatile Loading of Diverse Cargo into Functional Polymer Capsules (Adv. Sci. 1‐2/2015) - Richardson, Joseph J. (Adv Sci (Weinh), 2015)
A facile route for synthesizing a diverse array of cargo‐loaded polymer capsules using polymer‐stabilized calcium carbonate particles is introduced by Frank Caruso and co‐workers in article number 1400007. Cargo, ranging from anti‐cancer drugs to plasmid DNA, could be loaded in high quantities, making this technique promising for a variety of applications. [Image: see text]